Diagnostic concordance between MRI and electrovibratography of the temporomandibular joint of subjects with disc displacement disorders - Deregibus, A (The British Institute of Radiology., 2013)
OBJECTIVES: The aim of this study is to evaluate the diagnostic concordance of MRI and electrovibratography (EVG) of the temporomandibular joint (TMJ) in the diagnosis of articular disc displacement with reduction (ADDwR) and articular disc displacement without reduction (ADDw/oR). METHODS: 50 patients (12 males, 38 females; mean age 37.46 ± 15.64 years) with a hypothesis of disc displacement were selected. For each patient an MRI of the TMJ was performed. MRIs were evaluated sorting the 100 TMJs by kind of pathology (no pathology, ADDwR, ADDw/oR, and joint hypermobility). Afterwards, the patients had an EVG exam. The EVG exams were performed with vibration transducers over each TMJ, enabling simultaneous, bilateral recording of vibrations emanating from joint sounds during the opening and closing movements. The presence of a sound peak was compared with the MRI diagnosis of ADDwR, while a multipeak aspect was compared with ADDw/oR diagnosis using Cohen's kappa test. RESULTS: The presence of a peak-shaped track has high specificity for ADDwR (90.27%). The Cohen's kappa calculated for the ADDwR was 0.5615 (good–moderate). The presence of a multipeak-shaped track has low specificity (65.22%) and sensitivity (70.42%). The Cohen's kappa calculated for the ADDw/oR was 0.2992 (poor). CONCLUSIONS: The present study recommends the use of EVG to support the clinical diagnosis of a disc displacement with reduction when MRI is not available or when subjects cannot be investigated by MRI.